Chemical Changes Associated with Repetitive Re-Use of Vegetable Oil during Deep Frying of Bean Cake, Plantain and Yam - O.A, Osunrinade; K.O, Jimoh; J.O, Babalola (Journal of Food Technology Research, 2020)
Oil re-use is a common practice in households. Oxidative and hydrolytic reactions have been reported to cause significant changes in oil quality. This study was carried out to determine the chemical changes specific to beans cake (Vigna unguiculata), Plantain (Musa paradisiaca) and yellow yam (Discorea cayenensis) frying with repetitive re-use of oil. Refined vegetable and palm oil were used for five consecutive frying operations for bean cake, plantain and yam. Free fatty acids, iodine value, peroxide value and saponification value of the first, third and fifth frying operations were determined using standard methods. For refined vegetable oil, the FFA range for repeated frying operations obtained for bean cake, plantain and yam were 0.31-0.53, 0.37-0.52 and 0.40 to 0.53 % oleic respectively. While palm oil re-use had a range of 11.87 to 14.97 in the value of their FFA. Peroxide value (3.24- 4.92 meq/kg), Iodine value (91.09-107.00 mg/100g) and Saponification value (125.00-152.66 mgKOH/g) were obtained for re-use refined vegetable oil while Peroxide value (27.95-77.02 meq/kg), Iodine value (131.68-210.89 g/100g) and Saponification value (179.45-197.50 mgKOH/g) were obtained for re-use palm oil. Generally, frying operation led to increase in the FFA of refined vegetable oil. Frying operation for peroxide value significantly varied for all frying operation for plantain. Significant difference existed in iodine value at p<0.05 among frying operations for bean cake and yam. Changes in chemical properties of oil were affected by frying duration and food material fried.